ANALISIS STANDAR OPERASIONAL PROSEDUR PEMBERIAN KREDIT PADA ANGGOTA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) BHINNEKA KARYA PAMEKASAN - Siti Salama Amar (JURNAL AKUNTANSI DAN INVESTASI, 2016)
Giving credit is a cooperative effort of the most fundamental so that cooperatives need to provide an assessment of the customers who apply for credit loans, with an element of risk and uncertainty this causes is required a credit security. Standard Operating Procedure includes lending a Cooperative Credit Public Policy (CTP) of the cooperative, which among other things contains Precautionary Principle, Organizations and Credit Management, Credit Approval Policy, Development and Supervision, Management of Non Performing Loans. The focus of research into the main study, namely: how Standard Operating Procedure crediting at KPRI Member Bhineka Pamekasan work is already in line with Law No. 96 / Kep / M.KUKM / IX / 2004 Article 15. This study uses a qualitative approach with descriptive, the sample in this study was a sample intended or purposive sampling with the following criteria: (1) member who regularly deposit mandatory dues and principal, (2) members who are doing principal loan during the study period. The results of this study indicate that the lending procedures in KPRI Diversity Works Pamekasan are in accordance with Standard Operating Procedures established by KPRI Unity Works Pamekasan. But to guarantee such loans BPKB in KPRI Diversity work is not obliging as collateral. SOP should in KPRI Diversity work is to follow the SOP issued by Menperindangkop 2004.